Advanced age and high‐residual platelet reactivity in patients receiving dual antiplatelet therapy with clopidogrel or ticagrelor. (29th December 2015) - Verdoia, M.; Pergolini, P.; Rolla, R.; Nardin, M.; Schaffer, A.; Barbieri, L.; Marino, P.; Bellomo, G.; Suryapranata, H.; De Luca, G.
Abstract : Essentials Dual antiplatelet therapy (DAPT) in elderly patients requires balancing bleedings and thrombosis. Impact of age on high residual on‐treatment platelet reactivity (HRPR) on DAPT was studied. A reduced effectiveness of adenosine diphosphate antagonists was observed over 70 years of age. The occurrence of HRPR was increased among elderly patients with both clopidogrel and ticagrelor. Summary: Background: The aim of the present study was to evaluate the impact of age on platelet function and the occurrence of high residual on‐treatment platelet reactivity (HRPR) in patients treated with dual antiplatelet therapy (DAPT) using acetylsalicilic acid (ASA) and clopidogrel or ticagrelor. Methods: Patients treated with DAPT (ASA and clopidogrel or ticagrelor) were scheduled for platelet function assessment at 30–90 days post‐discharge. By whole blood impedance aggregometry, HRPR was considered for ASPI test values > 862 AU*min (for ASA) and adenosine diphosphate (ADP) test values > 417 AU*min (for ADP antagonists). Elderly patients were defined as those aged ≥ 70 years. Results: Among 494 patients on DAPT, 224 (45.3%) were ≥ 70 years old. ADP‐mediated platelet aggregation increased with decades of age (279.3 ± 148.6 vs. 319.6 ± 171.1 vs. 347.3 ± 190.1 vs. 345.7 ± 169.2), whereas no difference was observed for ASA response. A reduced effectiveness of ADP antagonists was observed among elderly patients; in fact, among the 117 patients displaying HRPR (23.7%), a higher prevalence was observed among patients over 70 years old (30.4% vs. 18.1%; adjusted odds ratio (OR) [95% confidence interval (CI)] = 2.19 [1.29–3.71]). Similar results were obtained among the 266 clopidogrel‐treated patients (38.5% vs. 27.9%; adjusted OR [95% CI] = 2.91 [1.46–5.8]) and in the 228 patients receiving ticagrelor (19.1% vs. 8.1%; adjusted OR [95% CI] = 2.55 [1.02–8.59]). Conclusion: In patients receiving dual antiplatelet therapy, advanced age is independently associated with a reduced effectiveness of ADP antagonists and a higher rate of HRPR with both clopidogrel and ticagrelor.